Decision Support System for the Location of Healthcare Facilities SitHealth Evaluation Tool - Dell'Ovo, Marta; Oppio, Alessandra; Capolongo, Stefano; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
The book examines an integrated approach for addressing decisions about the location of healthcare facilities. Supported by Geographic Information Systems (GIS) and Multi-Criteria Decision Analysis (MCDA), the approach provides comprehensive information on territory, taking into account the spatial dimensions. Due to the multiple criteria involved, site selection for urban facilities is a crucial topic in planning decision processes, especially for healthcare facilities. Healthcare provision policies generally fail to address the distribution of facilities within cities, entrusting decisions to various stakeholders. Moreover current evaluation tools focus on the intrinsic performances of healthcare structures, disregarding the extrinsic characteristics, namely those related to the location. Starting with a cross-disciplinary literature review, the book describes a multi-methodological approach for decision-making regarding the location of healthcare facilities, and presents an innovative evaluation tool that simultaneously considers functional, locational, environmental and economic issues, providing a comprehensive overview of the areas under investigation. .
Keywords: Practice of medicine; Facility management; Operations research; Decision making; Regional economics; Spatial economics; Urban geography; Practice and Hospital Management; Facility Management; Operations Research/Decision Theory; Regional/Spatial Science; Urban Geography / Urbanism (inc. megacities, cities, towns).